Avaliação de trajetória genética e da sensibilidade dos valores genéticos ás mudanças do nível nutricional da dieta em dois grupos de codornas de corte - Glaucyana Gouvea dos Santos (2010)
Two experiments were carried out with quail meat type lines EV1 and EV2 to evaluate the genetic trajectory and sensitivity of genetic values to changes in the nutritional levels of diets. Initially growth genetic trajectories were evaluated using random regression model, under animal model and genetic parameters estimates were obtained to establish the most adequate age for quail selection. Genetic parameter estimates were obtained using Dxmrr subroutine of the DFReml software using records from three generations of selection. For both genetic lines highest heritability estimates were obtained for body weight at 42 days of age, and genetic correlations between body weight at hatch and body weights recorded in other ages were all negatives and permanent environment correlation estimates were higher for EV2 genetic line. The results suggest that selection to increase body weight for EV1 line would be more efficient when undertaken at earlier ages, but for EV2 line the selection could be undertaken at 42 days of age with low response. The second study evaluated the sensitivity of genetic values of EV1 and EV2 meat type strains to changes in crude protein levels of diets (24 to 30%), using random regression models. Quails showing higher body weight genetic value in the average environment (crude protein level equal to zero in a scale varying from – 1 to 1) respond positively to an increase in crude protein level of diet, this change is more important for EV2 quails (higher slope) and of small magnitude for EV1 quails at 21 days of age. EV2 quails at 21 and 42 days of age showed remarked increase in the dispersion of breeding values as crude protein level increased in the diets, suggesting a genotype x protein level of diet interaction, while the EV1 quails showed this interaction effect only at 42 days of age. Genetic evaluations of quails fed specific diet crude protein level do not allow predictions of valid breeding values for quails fed other crude protein level of diet, except for EV1 quails at 21 days of age.